A sociedade cínica contemporânea e suas injunções nas subjetividades - Ribeiro, Karla Cristina Rocha (2012)
The present research hás the goal to analyse the contemporary cynic society and its injuctions in the subjective construction. We have the understanding that, in this society, the consumption society, cynism hás became the ideological link that embases subjective bonds and leads to modifications on the internal dynamic of individuals. So, to discuss the cynism, we made a historical filosofic investigation about this term, considering its meaning since its appearing - in Ancient Greece - until contemporaneity-as a sinonim for cheek and effrontery. This historic tension hás followed the politic and economic wave and made the current cynism the standart of living and being. In this scenario, the subjective construction passes for many transformations that promote the emergency of a sadic superego and a masoquist ego, in a dynamic that privileges a kind of unreachable pleasure in prejudice of a posible satisfaction for mankind. This is a participant and analitic research that uses as teoric references the Critic Theory of Frankfurt School and the Psychoanalysis, by Freud and Lacan's studiers.